Bolhas Racionais no Mercado de Combustíveis - Marcolino, Lucas Almeida (Universidade Federal de São Carlos, 2023)
With the emergence of flex-fuel vehicles, consumers now have a varied choice of fuels, adopting economic and environmental criteria when choosing between gasoline, ethanol and diesel. This factor resulted in fuel price speculation, which affected both consumption and the Government's policies to contain inflationary processes in recent years. The main objective of this work was to discuss and date the presence of speculative bubbles in the prices of gasoline, ethanol, diesel and LPG in the five regions of Brazil, using the Generalized Supreme Augmented Dickey-Fuller (GSADF) and GSADF Panel models for data in regional panel. The average resale prices made available by the National Petroleum, Natural Gas and Biofuels Agency (ANP) were used, with a weekly frequency starting on December 30, 2012 and ending on December 4, 2022. In the development, a historical survey was carried out and empirical studies of recent studies regarding different bubble detection methods for different assets. The panel models presented statistically significant results and made it possible to date bubbles for the five Brazilian regions, with periods of explosiveness in 2015, 2017, 2018 and 2021, indicating long periods of duration until the collapse of the bubbles. The results confirmed initial expectations and validated recent global events that would theoretically affect agents' speculative behavior.
Rational Bubbles in Fuels Market
Keywords: Painel GSADF; Bolhas especulativas; Combustível no Brasil; Speculative bubbles; Fuel in Brazil; Exuber package; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA